2022
DOI: 10.1021/acs.inorgchem.2c02805
|View full text |Cite
|
Sign up to set email alerts
|

1-(Nitratomethyl)-5H-tetrazole: A Highly Sensitive Ligand with Improved Oxygen Balance for Laser-Ignitable Coordination Compounds

Abstract: For the first time, the highly sensitive 1-(nitratomethyl)-5H-tetrazole (1-NAMT) was synthesized, representing the shortest possible 1-(nitratoalkyl)-5H-tetrazole with a combined nitrogen and oxygen content of 81.4%. Compared to its related ethyl derivative, 1-(nitratoethyl)-5H-tetrazole, it exhibits improved oxygen balance, resulting in higher detonation parameters. 1-NAMT was thoroughly analyzed by single-crystal diffraction experiments accompanied by elemental analysis, IR spectroscopy, and multinuclear (1H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The difference is that the ligands here are diverse. First, the nitrogen heterocyclic ring itself may have coordination sites, especially the tetrazole ring. Second, groups with strong coordination ability, such as −NH 2 , −NHNH 2 , and −CONHNH 2 , are added to the nitrogen heterocyclic ring through substitution reaction so as to form metal coordination bonds with central ions. Ag + , Cu 2+ , Ni 2+ , Co 2+ , Cd 2+ , Pb 2+ , and Mn 2+ are commonly used as central metal ions. …”
Section: Introductionmentioning
confidence: 99%
“…The difference is that the ligands here are diverse. First, the nitrogen heterocyclic ring itself may have coordination sites, especially the tetrazole ring. Second, groups with strong coordination ability, such as −NH 2 , −NHNH 2 , and −CONHNH 2 , are added to the nitrogen heterocyclic ring through substitution reaction so as to form metal coordination bonds with central ions. Ag + , Cu 2+ , Ni 2+ , Co 2+ , Cd 2+ , Pb 2+ , and Mn 2+ are commonly used as central metal ions. …”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of research, multidisciplinary development, and new requirements, more and more new materials have been used in primary explosives. , Among them, energetic coordination compounds (ECCs) have entered the perspective of researchers due to their unique structure and performance advantages . Because of its simple preparation, good performance, easy amplification, and high purity, it is favored by researchers, and Klapötke has made outstanding contributions in this regard. …”
Section: Introductionmentioning
confidence: 99%
“…In the field of ECCs, Klapötke have made significant contributions, with their research focusing on ECCs using tetrazole derivatives as ligands. [11][12][13] However, since the [N] in the tetrazole ring is connected, it contains a lot of chemical potential energy, and the derived groups are often high-energy explosive groups, such as 1-(nitromethyl)-5H-tetrazole, 14 1-(azidomethyl)-5H-tetrazole, 15 and 1-vinyl-5H-tetrazole, 16 meaning that the ligand itself shows relatively high explosive performance. Therefore, although these [ClO 4 − ]-based complexes have high energy, they are very sensitive to mechanical stimuli, and we have found that complexes prepared using stereoisomers have different structures and properties.…”
Section: Introductionmentioning
confidence: 99%